Tension at the table: 1 Corinthians 11:23–32. (August 2019) - Harader, Joanna
Paul's presentation of the communion meal in 1 Cor 11:23–32 highlights tensions we experience as we participate in the Lord's Supper today: situational tension in re-enacting a conflicted meal and remembering a violent event, a tension between memory and hope, a painful tension for survivors of sexual abuse with the use of "body" and "blood" language in both Scripture and liturgy, and a tension between an insistence on the egalitarian nature of the meal alongside warnings of exclusionary judgment for any who eat while "unworthy." The first two tensions are biblical and are to be explored and embraced in sharing the Lord's Supper. The second two tensions result from unintended consequences and misinterpretation, and should be discerned and alleviated to maintain a spiritually healthy and faithful communion liturgy.